49.2k views
11 votes

9(x+1) -4x = 5-(x-3)

User Gjacquez
by
4.9k points

1 Answer

6 votes

Answer:


x=(-1)/(6)

Explanation:


9(x+1) -4x = 5-(x-3)


9(x+1) -4x = 5-(x-3) \\


9x+9\cdot1-4x=5-\left(x-3\right)


9x+9-4x=5-\left(x-3\right)


\left(9x-4x\right)+9=5-\left(x-3\right)


5x+9=5-\left(x-3\right)


5x+9=5-x+3


5x+9=-x+\left(5+3\right)


5x+9=-x+8


5x+9=-x+8


5x+9+x=-x+8+x


5x+x+9=-x+8+x


6x+9=-x+8+x


6x+9=-x+x+8


6x+9=8


6x+9=8


6x+9-9=8-9


6x=8-9


6x=-1


(6x)/(6)=(-1)/(6)


x=(-1)/(6)

User Sajjan Sarkar
by
5.6k points